"Medical Computer Vision: Algorithms for Big Data" : International Workshop, MCV 2015, held in conjunction with MICCAI 2015, Munich, Germany, October 9, 2015 : revised selected papers /: International Workshop, MCV 2015, held in conjunction with MICCAI 2015, Munich, Germany, October 9, 2015 : revised selected papers. ([2016]) - Unknown
No abstract available